Comparative analysis of tangentially laser-processed fluted polycrystalline diamond drilling tools. (August 2016) - Warhanek, M.; Walter, C.; Hirschi, M.; Boos, J.; Bucourt, J.F.; Wegener, K.
Graphical abstract: Highlights: Tangential picosecond laser processing of PCD helical drilling tools. Comparative analysis of cutting edge radii, surface quality and process forces. Drilling experiments in zirconium dioxide reveal ductile material removal mechanism. Wear analyses show significant benefit of PCD tools regarding the tool lifetime. Abstract: Ultrashort-pulsed laser ablation is increasingly applied in various fields of science and technology. For the purpose of processing ultra-hard materials, such as diamond and cubic boron nitride (CBN) composites, lasers have the decisive advantage of wear-free material removal. The availability of high-powered ultrashort-pulsed laser sources enables the efficient applications of tangential processing strategies to generate complex 3D geometries. Compared to the conventionally applied 2.5D volume ablation strategy, the resulting workpiece form tolerance, repeatability, and surface quality is increased significantly and does not depend on the quality of the initial surface. This makes tangential processing an ideal choice for high-precision finishing processes. This paper presents a set of processes for the tangential ablation of characteristic twist drill features, such as helical grooves, flank faces and notches at the chisel edge. The processes have been implemented using a pulse duration of 12 ps, infrared laser source with an average power of 35 W average power for generating PCD tools. A comparative drilling study in zirconium dioxide (ZrO2 ) with diamond-coated tungsten carbide tools and solid PCD tools processed by electrical discharge machining is conducted to assess the performance of the laser-processed PCD tools.